Clinical analysis of 100 medicolegal cases. Issue 6917 (4th December 1993) - Neale, G
Abstract : OBJECTIVE--To find the reasons for legal claims against hospital doctors. DESIGN--Prospective analysis of requests for medical opinion submitted by solicitors during 1984-93 on legal claims against hospital doctors. SUBJECTS--100 successive cases: 98 from the United Kingdom and two from the Republic of Ireland. MAIN OUTCOME MEASURES--Principal underlying causes of claims. RESULTS--In 44 cases there was no serious clinical error. Of the 56 cases of clinical fault, seven were a failure of communication by doctors, 15 were an isolated error in otherwise good clinical management, 21 were errors that might not have occurred with better control of clinical practice (doctors exceeding their competence, poor clinical judgment, and poor teamwork), and 13 were major errors due to carelessness or incompetence. In 34 cases there was evidence of clinical fault that might escape clinical audit and medicolegal processes. Most of these legal claims have been or are likely to be withdrawn: only five plaintiffs have settled out of court, and 11 are pursuing their actions. CONCLUSIONS--To reduce the incidence of errors, hospital doctors should consult colleagues about difficult cases and specialists should maintain a broad interest in disease. The NHS clinical complaints procedure should be extended to cover potential claims, and serious cases should be subject to independent external assessment by experienced consultants.